Bile Acids Induce Alterations in Mitochondrial Function in Skeletal Muscle Fibers - Valero-Breton, M; Cabello-Verrugio, C; Tacchi, F; Abrigo, J (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Cholestatic chronic liver disease is characterized by developing sarcopenia and elevated serum levels of bile acids. Sarcopenia is a skeletal muscle disorder with the hallmarks of muscle weakness, muscle mass loss, and muscle strength decline. Our previous report demonstrated that deoxycholic acid (DCA) and cholic acid (CA), through the membrane receptor TGR5, induce a sarcopenia-like phenotype in myotubes and muscle fibers. The present study aimed to evaluate the impact of DCA and CA on mitochondrial mass and function in muscle fibers and the role of the TGR5 receptor. To this end, muscle fibers obtained from wild-type and TGR5−/− mice were incubated with DCA and CA. Our results indicated that DCA and CA decreased mitochondrial mass, DNA, and potential in a TGR5-dependent fashion. Furthermore, with TGR5 participation, DCA and CA also reduced the oxygen consumption rate and complexes I and II from the mitochondrial electron transport chain. In addition, DCA and CA generated more mitochondrial reactive oxygen species than the control, which were abolished in TGR5−/− mice muscle fibers. Our results indicate that DCA and CA induce mitochondrial dysfunction in muscle fibers through a TGR5-dependent mechanism. © 2022 by the authors.